Ptychography retrieval of fully polarized holograms from geometric-phase metasurfaces - Qinghua Song (Nature Portfolio, 2020)
Controlling light with planar elements requires full polarization channels and reconstruction of optical signals. Here, the authors have demonstrated a general method relying on pixelated metasurfaces that enables wavefront shaping with arbitrary output polarization, allowing full utilization of polarization channels.